2018
DOI: 10.1103/physrevb.97.195425
|View full text |Cite
|
Sign up to set email alerts
|

Electrical spin manipulation in graphene nanostructures

Abstract: We propose a mechanism to drive singlet-triplet spin transitions electrically in a wide class of graphene nanostructures that present pairs of in-gap zero modes, localized at opposite sublattices. Examples are rectangular nanographenes with short zigzag edges, armchair ribbon heterojunctions with topological in-gap states, and graphene islands with sp 3 functionalization. The interplay between the hybridization of zero modes and the Coulomb repulsion leads to symmetric exchange interaction that favors a single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 66 publications
(148 reference statements)
1
33
1
Order By: Relevance
“…Such peaked steps are characteristic of Kondo-like fluctuations of the spin once the anisotropy energy has been overcome by tunneling electrons (i.e. out of equilibrium) 3134 . The more pronounced signal for either particle tunneling (over ZZ) or for hole tunneling (over PC) indicates the spins system lies out of particle-hole symmetry point, with E F closer to the corresponding singly unoccupied or singly occupied (SO) state, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Such peaked steps are characteristic of Kondo-like fluctuations of the spin once the anisotropy energy has been overcome by tunneling electrons (i.e. out of equilibrium) 3134 . The more pronounced signal for either particle tunneling (over ZZ) or for hole tunneling (over PC) indicates the spins system lies out of particle-hole symmetry point, with E F closer to the corresponding singly unoccupied or singly occupied (SO) state, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the most promising for applications are the armchair GNR, denoted as N -AGNRs, with N the number of C atoms along the width of the ribbon [17][18][19][20][21][22]. This bottom-up approach has been successfully applied to build more complex systems, [23] such as GNRs with a specific periodic modulation in their width. [24] Recently, two works by Grönig et al [25] and Rizzo et al [26] demonstrated that periodic superlattices of N -AGNR/M -AGNR (different width) host topologically protected edge states, in close analogy to the Su-Schieffer-Heeger (SSH) model of polyacetylene [27].…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, graphene functionalized with sp 3 defects, such as atomic hydrogen, is also predicted to host zero modes with an individual electron, forming thereby a S = 1/2 defect 16,25 . Some graphene grain boundaries are also predicted to host zero modes and local moments 22,29,35,38 , as well as some interfaces between ribbons of different width 43,46 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a consensus, in the theory front, that graphene local moments arise in graphene systems where sublattice imbalance is broken 3,8,12,50 , or in systems where localized states arise close to the Fermi energy, such as grain boundaries 22,29,35,38 . These local moments are predicted to have very interesting properties: a very elegant interplay between sublattice and spin polarization 8,11,13,31 , prone to electrical control 6,18,48 and electrically driven spin resonance 46 , exotic Yu-Shiba-Russinov states when proximitized by a superconductor 39 , domain walls with fractional charge 42 , and even potential for quantum computing 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation